Development and exemplification of a model for Teacher Assessment in Primary Science. Issue 14 (22nd September 2017) - Davies, D. J.; Earle, S.; McMahon, K.; Howe, A.; Collier, C.
ABSTRACT: The Teacher Assessment in Primary Science project is funded by the Primary Science Teaching Trust and based at Bath Spa University. The study aims to develop a whole-school model of valid, reliable and manageable teacher assessment to inform practice and make a positive impact on primary-aged children's learning in science. The model is based on a data-flow 'pyramid' (analogous to the flow of energy through an ecosystem), whereby the rich formative assessment evidence gathered in the classroom is summarised for monitoring, reporting and evaluation purposes [Nuffield Foundation. (2012). Developing policy, principles and practice in primary school science assessment . London: Nuffield Foundation]. Using a design-based research (DBR) methodology, the authors worked in collaboration with teachers from project schools and other expert groups to refine, elaborate, validate and operationalise the data-flow 'pyramid' model, resulting in the development of a whole-school self-evaluation tool. In this paper, we argue that a DBR approach to theory-building and school improvement drawing upon teacher expertise has led to the identification, adaptation and successful scaling up of a promising approach to school self-evaluation in relation to assessment in science.